Manejo inicial del politraumatizado - Cortés M., César; Acuña R., Loreto; Álvarez M., Fernando; Álvarez L., Natalia (Revista Hospital Clínico Universidad de Chile, 2014)
Trauma is today the first cause of death in young population; Motor vehicle crashes (MVC’s) are the main specific cause. The initial approach of the trauma patient takes place in the prehospital and hospital environment, following a systematic evaluation and priorizing some systems above others. Primary evaluation (with the classic sequence: ABCDE), sets intervention priorities thatultimately target a reduction in trauma early mortality. The in-corporation of ultrasonography in the evaluation of the trauma patient, has been fundamental in searching for injuries that may have been overlooked in the primary evaluation. Injuries that compromise ventilation may cause hypoxemia and hemodynamic instability. Early bleed control is the main therapeutic target in the trauma patient with active hemorrhage, which leads to reduction of early mortality and also prevents future complications. Fluid resuscitation is the main intervention to restore tissue perfusion. Also, the use of transfusional therapy, permissive hypotension and tranexamic acidmust also be considered. Emergency Ultrasound is today a fundamental instrument in the initial trauma patient evaluation, because it greatly contributes to the evaluation of ventilatory derangement and hemodynamic instability causes. Finally, one must remember that trauma is a dynamic process, and therefore reevaluating is imperative, especially because findings of neurological deficit or deterioration in time, will ultimately conduct to the diagnose of injuries that cause brain hypoperfusion.